The political theology of entropy: A Katechon for the cybernetic age. (February 2020) - Bates, David
The digital revolution invites a reconsideration of the very essence of politics. How can we think about decision, control, and will at a time when technologies of automation are transforming every dimension of human life, from military combat to mental attention, from financial systems to the intimate lives of individuals? This article looks back to a moment in the 20th century when the concept of the political as an independent logic was developed, in a time when the boundaries and operations of the classic state were in question. At the same moment, a whole new technological era was opened up with the emergence of intelligent machines and computers in the postwar cybernetic age. Technology, and cybernetics in particular, loomed large in Carl Schmitt's articulation of the concept of the political, while the problem of radical open decision was at the heart of influential cybernetic approaches to politics. Linking these was the idea of entropic decay. Schmitt's invocation of the theological concept of the Katechon, who restrains chaos in the time before Christ's return, in fact exemplifies the new understandings of order in a cybernetic age facing new challenges of technology in a globalized condition.